Surface-activated bovine platelets do not spread, they unfold. - Grouse, L. H. (1990)
The present study has examined the response of bovine platelets to surface activation and compared it to the reaction of human cells. Human platelets react to surfaces by losing their discoid shape, extending pseudopods, converting to dendritic forms, and finally, spreading into thin films resembling pancakes. Bovine platelets do not spread, they unfold. Surface activation causes them to transform from discs to irregular, flattened shapes resembling dendritic platelets, but they are unable to fill in spaces between pseudopods, a step required for spreading. Bovine platelets lack the surface-connected open canalicular system (OCS), which serves as a reservoir of membrane for human platelet spreading. Its absence may be the major factor in the failure of bovine platelet spreading, but there are other possible factors. Circumferential microtubules are more resistant to disassembly in surface-activated bovine than human cells, and their stability as rings or fractured bundles may limit spreading. Actin filament assembly is similar in human and bovine platelets, but the organization is different. Human platelets form a peripheral weave of actin that expands the membrane between pseudopods. A peripheral weave does not form in surface-activated bovine platelets. The absence of the OCS and differences in cytoskeletal organization in bovine platelets may also affect spreading of the surface membrane. Fibrinogen-gold (Fgn-Au) probes added to spread human platelet move from pseudopods and the cell margin toward the center and concentrate in the OCS. Fgn-Au particles bind to surface-activated bovine cells, but move very little, or not at all. All of these factors may contribute to the inability of bovine platelets to react to surfaces by spreading like human cells, but absence of the OCS appears to be the major cause.